Comparison of treatment strategies for patients with limited-stage small cell lung cancer who received chemotherapy - Wei, Shenhai; Wei, Bo; Tian, Jintao; Song, Xiaoping; Wu, Bingqun; Hu, Pengcheng (Translational Cancer Research; Vol 9, No 2 (February 28, 2020): Translational Cancer Research, 2020)
Background: The standard care for limited-stage small cell lung cancer (SCLC) is unclear. The purpose of this study is to compare the outcome for patients receiving chemotherapy alone, chemotherapy plus surgery (CS), chemotherapy plus radiation (CR), or chemotherapy plus surgery and radiation (CSR) for limited-stage SCLC. Methods: Patients with T1-4N0-2M0 SCLC who received chemotherapy from 2004 to 2014 were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database. The overall survival (OS) of these patients, stratified by different stage, was compared in accordance to the method of receiving different treatments using Kaplan-Meier method and Cox regression analysis. Results: A total of 7,204 patients were included, where 1,347 (18.7%) patients received chemotherapy alone, 296 (4.1%) undergone CS, 5,296 (73.5%) patients were subjected to CR and 267 (3.7%) patients were managed by the three combination of CSR. Chemotherapy alone was associated with the worst survival in comparison to the other two method of combination i.e., chemotherapy with radiation or surgery. When compared with CR, CS had no survival benefit in patients with stage in excess of T1-2N0 disease, but was associated with improved 5-year OS in patients with T1-2N0 disease, which ranged from 29.1% to 54.3% (P